Colorectal Cancer Incidence: Does Iran Follow the West? - Mohammad Mohammadianpanah (Shiraz University of Medical Sciences, 2015)
Context Colorectal cancer (CRC) is the third most prevalent cancer worldwide which is less common in the Middle East. It is also the second leading cause of cancer-related mortality and represents a major public health problem in developed countries. Objectives The present review aimed to explore the differences among the reports on number and age standardized incidences of CRC in both sexes in different areas of Iran to find the incidence trend of this cancer. Data Sources All the published reports citing the incidence of CRC in Iran were collected by conducting a literature search in international databases. Study Selection English articles were included where there was a clear definition of the population of patients under study and where the criteria for diagnosing CRC were well described. Data Extraction One author read each paper and extracted several studies and then the studies suitable for inclusion were reported in three categories. Results We identified 181 independent studies dating back to 2003; 168 full text articles were assessed for eligibility. However, 136 full text articles were excluded due to different reasons. Finally, 26 studies were suitable for inclusion in the analysis. The highest and lowest (age standardized rates) ASRs were respectively 3.4 and 2.6 in males and 11.42 and 10.56 in females. Time showed a slightly increasing trend in recent years. Conclusions Although Iran was expected to have a low incidence rate of CRC, recent studies revealed a slightly increasing trend for the incidence rate of CRC. This finding shows the necessity to consider CRC screening as an important issue in health policy priorities.